Influence of Summer Green Manuring on Soil Nematode Population under Rice-Wheat Cropping System (Indian Journal of Nematology, 2024)
Experiments were conducted to study effect of incorporation summer green manuring on nematode population and plant growth of rice infested with rice root-knot nematode, Meloidogyne graminicola. Plant parts viz., shoot and roots of Crotalaria were used to incorporate into the soil. Total nematode population and plant growth parameters (shoot and root length, shoot and root weight) were recorded at 60 day after inoculation (DAI). In general, all the treatments increased the plant growth parameters significantly compared to control plants. Maximum increase in plant growth parameters was observed in treatment, where leaf and roots of C. juncea were incorporated simultaneously during transplanting of rice seedlings. The number of galls formed on rice roots was reduced in all the treatments compared to control (34.25), with maximum reduction (85.2%) in treated plants. Available nitrogen,phosphorus and potassium, organic carbon and % organic matter content of soil in pots of third treatment was significantly higherwhere Crotalaria were grown for 45 days and both leaves and roots of same plants incorporated into soil. Thus, the same treatmentwas studied under field conditions, along with mungbean as green manure crop and fallow as a recommended practice for nematodecontrol. In this it was clear that Crotalaria was very effective compared to mungbean as well as fallow. The cultivation of C. junceaas a green manure crop for direct seeding or intercrops, or as organic soil amendment, can reduce or even eliminate plant parasiticnematodes, rice root-knot nematode.